2022
DOI: 10.1002/ame2.12233
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory effect of gut microbes on blood pressure

Abstract: Hypertension is an important global public health issue because of its high morbidity as well as the increased risk of other diseases. Recent studies have indicated that the development of hypertension is related to the dysbiosis of the gut microbiota in both animals and humans. In this review, we outline the interaction between gut microbiota and hypertension, including gut microbial changes in hypertension, the effect of microbial dysbiosis on blood pressure (BP), indicators of gut microbial dysbiosis in hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 215 publications
0
5
0
2
Order By: Relevance
“…Similarly, a 4.5% decline in diastolic pressure was also found in this subset of participants from the test arm, although this decrease was not statistically significant [Figure 3B]. It has been reported that increase in Lactobacillus and Bifidobacteria are associated with lower blood pressure 46 . Interestingly, gut microbiota analysis of these participants showed increased abundance of phylum Firmicutes [Lactobacillus is member of this phylum] and Actinobacteria [Bifidobacteria is a member of this phylum] [Figure 4A].…”
Section: Change In the Blood Pressure Parametersmentioning
confidence: 53%
See 1 more Smart Citation
“…Similarly, a 4.5% decline in diastolic pressure was also found in this subset of participants from the test arm, although this decrease was not statistically significant [Figure 3B]. It has been reported that increase in Lactobacillus and Bifidobacteria are associated with lower blood pressure 46 . Interestingly, gut microbiota analysis of these participants showed increased abundance of phylum Firmicutes [Lactobacillus is member of this phylum] and Actinobacteria [Bifidobacteria is a member of this phylum] [Figure 4A].…”
Section: Change In the Blood Pressure Parametersmentioning
confidence: 53%
“…Gut microbiota dysbiosis has been reported in patients with high blood pressure 45 . Gut microbiota modulation has been shown to impact blood pressure 46 . Hence, we wanted to investigate if microbiota based nutritional intervention would impact the blood pressure parameters in the participants of the test arm.…”
Section: Change In the Blood Pressure Parametersmentioning
confidence: 99%
“…Microbes of the genus Blautia have been previously associated with elevated BP in cross‐sectional animal and human studies (Yan et al., 2022). Blautia microbes metabolize carbohydrates with main end‐products being acetic acid, succinic acid, lactic acid, and other SCFAs (Freitas et al., 2022; Liu et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…According to the study by Li et al, hypertensive individuals had decreased microbial richness and diversity, Prevotella-dominated gut enterotype, and overgrowth of bacteria such as Prevotella and Klebsiella [ 14 ]. Another research also reported the correlation between Prevotella and elevated blood pressure [ 26 ]. However, currently there’s no research on Preotella copri in hypertension patients, but it may play an essential role in triggering the inflammatory response in disease such as rheumatoid arthritis [ 27 ].…”
Section: Discussionmentioning
confidence: 99%